UTILIZATION OF CITRIC ACID AS BONDING AGENT IN SEMBILANG BAMBOO (Dendrocalamus giganteus Munro) PARTICLEBOARD PRODUCTION - Firda A. Syamani; Agus Z. Arifqi; Sudarmanto Sudarmanto; Lilik Astari; Kurnia W. Prasetiyo; Mohamad Gopar; Ismadi Ismadi; Sukma S. Kusumah; Subyakto Subyakto; Yusuf S. Hadi; Kenji Umemura; Sasa S. Munawar; Mohd. H. Hussin (Indonesian Journal of Forestry Research, 2022)
Citric acid was utilized as a bonding agent in the production of Sembilang bamboo particleboard. The limitation in using bamboo for particleboard production is that the silica content in bamboo skin can accelerate particleboard processing machines' bluntness and reduce particle adherence in particleboard manufacturing. This research aimed to investigate the influence of bamboo skin and citric acid content on the characteristics of Sembilang bamboo particleboard. Particleboards were prepared using bamboo particles (type A) and unskinned bamboo particles (type B). The citric acid solution (59%) was sprayed over the surface of bamboo particles to obtain three different levels of citric acid, i.e., 15, 20, and 25 % (based on bamboo particles’ dry weight). The Sembilang bamboo particleboards were manufactured using a hot-pressing machine at 200°C, 5 MPa for 10 min. The particleboard targeted density was 0.8 g/cm3. The type B particleboards’ internal bond (IB), modulus of rupture (MOR), water absorption (WA), and thickness swelling (TS) were superior compared to the type A particleboards. This was influenced by the lower concentration of silica in type B particleboards, which tend to allow an intimate contact area among particles and citric acid then produced better quality particleboards compared to type A particleboards. The type B particleboards met the obligation of JIS A 5908 for type 18 particleboard in terms of modulus of rupture, modulus of elasticity, and internal bond, however, only fulfilled the type 8 particleboard in terms of screw holding power. The physical properties of Sembilang bamboo particleboard were also improved when using type B bamboo particles and adhered with citric acid at a level of 25%.